Investigando como e quais conhecimentos os docentes devem mobilizar em suas práticas de forma a oportunizar o desenvolvimento do pensamento algébrico no Ensino Fundamental: anos iniciais - Silva, Anderson Adelmo da (2022)
This qualitative approach research aims to understand how and what teaching knowledge are mobilized by a group of teachers that works in a municipal school in São Paulo to build some teaching strategies that will try to promote the development on/of the Algebraic thought on children aged six to ten years old. Considering the problem and our research goal, we present the teacher that teaches math as a subject and Teacher Knowledge, with emphasis on the relationship between knowledge of topics from the Elementary Theory of Numbers for the development of Algebraic Thinking, as a theme. We adopt the MTSK (Mathematics Teacher’s Specialized Knowledge) the theoretical reference, establishing interfaces, with the curriculum, formation, identity and the teacher professional development. To reach our main goal we decided to delimit the following specific objectives: to present the relationship between the topics of Elementary Theory of Numbers (multiples, divisors, prime and composite numbers, Fundamental Theorem of Arithmetic and mod m congruence) as underlying themes for the development of Algebraic Thinking; build a theoretical framework relating MTSK and Knowledge mobilized by teachers who teach Mathematics for the development of Algebraic Thinking; carry out a training course focusing on the Curriculum of the City of São Paulo and the development of Algebraic Thinking. We meet the first two specific objectives in our theoretical framework and, to obtain data, we carried out field research, proposing a formative course of thirteen meetings in a Municipal School Unit in the East Zone of São Paulo, in collective time, in which they participated. nineteen teachers, being twelve subjects of our research (remaining nine in our analysis) and seven teachers from other areas who made up the study group, but they were not subjects of this investigation, as they are not professors who teach Mathematics. We present as a secondary question to our main goal: the teachers use knowledge of topics of Elementary Theory of Numbers in situations that address aspects relevant to the development of Algebraic Thinking? Based on the triangulation between field research data, our theoretical framework and the literature review, we infer those teachers who teach Mathematics perceive, when exposed as learners in situations with the potential to develop their Algebraic Thinking, practices that meet the needs of his students. The Mathematical Knowledge (MK) subdomains, to enable the application of its Pedagogical Content Knowledge (PCK) and its subdomains, proved to be incipient to elaborate strategies with the objective of propitiating the development of the Algebraic Thinking